Prevalence of risk for dyslexia, risk for dyscalculia, and their comorbidity in Spanish primary education: gender difference and socioeconomic status - Loredo, Mariana; Luque, Juan L.; Giménez, Almudena; López-Pérez, P. Javier (Frontiers in Psychology, 2025)
Dyslexia and dyscalculia frequently co-occur; however, population-based estimates from Spain, remain scarce. This study aims to assess the prevalence of risk for dyslexia (RDyx), risk for dyscalculia (RDC), and their comorbidity (RDyx+RDC) and to evaluate their distributions by gender and socioeconomic status. A total of 691 Spanish students in 5th–6th grade were assessed with computerized screening tasks in reading and mathematics. Risk groups were defined using a cut-off of −1 SD (16th percentile) within each domain. Prevalence was 8.5% (6.6–10.9%) for RDyx, 4.2% (2.8–6.0%) for RDC, and 2.0% (1.1–3.4%) for RDyx+RDC. Comorbidity exceeded chance expectations and was asymmetrical: 48.3% of children with RDC also presented reading difficulties, while 23.7% of children with RDyx showed concurrent math difficulties. Gender effects were significant for RDC, with girls showing higher odds than boys (OR = 3.16), whereas no significant gender effect was observed for RDyx (OR = 1.56). Socioeconomic status showed a marginal effect in RDyx, but no effects were observed for RDC or comorbidity. These results provide the first population-based prevalence estimates of RDyx, RDC, and their comorbidity in Spanish primary education and underscore the value of risk-based digital screening at the school level.